Semantic Assessment of the Barkin Index of Maternal Functioning in a Medically Underserved Obstetric Population. Issue 2 (21st September 2015) - Barkin, Jennifer L.; Willis, Gordon B.; Hawkins, Kristina C.; Stanfill‐Thomas, Tiffany; Beals, Laura; Bloch, Joan R.
Abstract : Purpose: This study aims to evaluate the fitness of the Barkin Index of Maternal Functioning (BIMF) for postpartum functional assessment in a low‐income obstetric population in medically underserved, Central Georgia (USA). Design and Methods: Cognitive interviewing, a best practices approach to instrument development and validation, was performed on 24 new mothers. Findings: The BIMF was comprehensible to this population of disadvantaged women. Practice Implications: The BIMF has broad appeal due to its comprehensibility, patient‐centered assessment style, and psychometric profile. Method of questionnaire administration and characteristics of the study and/or patient population should routinely be considered when implementing any type of self‐reported health screening.